Analysis of inventory models to improve customer delivery performance of a supply chain system - Ashwini (2017)
Supply chain has been gaining growing importance in all companies as the optimized operation of supply chain has a direct relationship with the profits earned by the company. The supply chain of a company regulates the productivity, labour and customer service related costs. Customer satisfaction is integral for the progression of any company. When a customer receives an on-time delivery and products of optimal quality, they would have higher satisfaction with the service and are more likely to continue obtaining services from the company. This hence results in the company earning customer loyalty and gaining a better reputation in the market. As such, this will in turn increase the number of customers they earn and increase the revenue of the company as a whole. Furthermore, faster delivery rates are seen to reduce the purchasing cost in a supply chain and subsequently reduce the purchasing cost incurred. This ultimately reduces the holding cost, which usually makes up to 25% of the inventory costs. Therefore, the optimum amount of safety stock level should be maintained so as to prevent a situation of stock-out and at the same time minimize the holding cost of the inventory. In order to achieve an optimized operation of supply chain via fulfilling customer delivery performance and reducing the cost incurred, the aforementioned factors need to be kept at their ideal amounts. In this project, the author will use the influence of delivery time and safety stock level in the inventory models, Base-stock and QR on the expected inventory and customer delivery performance. This is fundamentally achieved via looking at the service level attained by the company. These two models are used as demand is assumed to be stochastic. The author will employ a computer program to study the impact of the variation of different factors on service level. She will then proceed to discuss the results and observations obtained after running the variations in the program. Upon conclusion of the research, the author gives overall credit to the company’s consideration and perception of its own set of aims and goals. It is this very set of aims and goals that will essentially determine the quantity each of the factors need to be kept which in turn affects the customer delivery performance.